Association of Thrombolysis in Myocardial Infarction (TIMI) Risk Score with Angiographic Severity of Coronary Artery Disease In Patients with Non-ST Elevation Acute Coronary Syndrome - Bashiruddin, ABK; Chowdhury, Mohammad Ibrahim; Bhattacharjee, Biplob; Shahin, Abul Hossen; Ahsan, Syed Ali; Mandal, MRM; Dhar, Sukanta; Mahmud, Iqbal; Hossain, Md Sahadat (University Heart Journal, 2019)
Background: Clinical guidelines recommend that optimal management of acute coronary syndrome (ACS) should include patient risk stratification. Predicting the anatomical extension of coronary artery disease (CAD) is also potentially useful for clinical decision. Objective: The objective of our study was to determine whether the TIMI risk score correlates with the angiographic extent and severity of CAD in patients with NSTE- ACS. Materials and Methods: This was a cross-sectional observational study carried out in the Department of Cardiology, Chattogram Medical College Hospital (CMCH) from September 2017 to May 2018. A total of 200 patients diagnosed with NSTE- Acute Coronary Syndrome were included as sample by purposive sampling method. TIMI risk score for each patient was calculated and the patients were stratified into 3 groups according to the TIMI risk score: low risk (0-2); intermediate risk (3-4); high risk (5-7). The severity of the CAD was assessed by Vessel score and Gensini score. Result: The mean ± SD of the age of study population was 53.7 ±10.8 years (range 37–77) and 142 (71%) were male. Regarding cardiovascular risk factors, 137 (68.5%) patients had diabetes mellitus, 83 (41.5%) had dyslipidaemia, 155 (77.5%) had hypertension, 136 (68%) were current smoker and 70 (35%) had a family history of CAD. The Gensini score was higher in patients at high risk TIMI group (p<0.001). Moreover, there was a signiûcant positive correlation between the TIMI and Gensini score (r=0.446,p<0.001). TIMI score can predict significant CAD moderately well (area under the curve 0.661, p=0.001). Patients with TIMI score > 4 were more likely to have significant three vessel CAD (65.9%) versus those with TIMI risk score 3-4 (17.9%) and TIMI risk score < 3 (2%) (p< 0.001). Conclusion: Study showed the TIMI score is significantly correlated with the extent of CAD as assessed by the Gensini score. It is accurate for predicting severe CAD among NSTE-ACS patients. University Heart Journal Vol. 15, No. 2, Jul 2019; 68-73